2007
DOI: 10.1016/j.cell.2007.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Tumor Cell Mitochondrial Homeostasis by an Organelle-Specific Hsp90 Chaperone Network

Abstract: Molecular chaperones, especially members of the heat shock protein 90 (Hsp90) family, are thought to promote tumor cell survival, but this function is not well understood. Here, we show that mitochondria of tumor cells, but not most normal tissues, contain Hsp90 and its related molecule, TRAP-1. These chaperones interact with Cyclophilin D, an immunophilin that induces mitochondrial cell death, and antagonize its function via protein folding/refolding mechanisms. Disabling this pathway using novel Hsp90 ATPase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
645
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 408 publications
(670 citation statements)
references
References 38 publications
24
645
0
1
Order By: Relevance
“…Pridgeon et al (2007) report stable complex formation between PINK1 and TNF-receptor-associated protein 1 (TRAP1). TRAP1 is a mitochondrial molecular chaperone also known as heat shock protein 75 (Hsp75) that modulates the permeability transition pore to inhibit mitochondrial-associated cell death (Kang et al, 2007). In PC12 cells, PINK1 binds and co-localizes with TRAP1 in mitochondria and phosphorylates TRAP1.…”
Section: Other Mitochondrial Partners Of Pink1 In Mitochondrial Protementioning
confidence: 99%
“…Pridgeon et al (2007) report stable complex formation between PINK1 and TNF-receptor-associated protein 1 (TRAP1). TRAP1 is a mitochondrial molecular chaperone also known as heat shock protein 75 (Hsp75) that modulates the permeability transition pore to inhibit mitochondrial-associated cell death (Kang et al, 2007). In PC12 cells, PINK1 binds and co-localizes with TRAP1 in mitochondria and phosphorylates TRAP1.…”
Section: Other Mitochondrial Partners Of Pink1 In Mitochondrial Protementioning
confidence: 99%
“…5 Little is known about TRAP1 signal transduction: the first most important finding on TRAP1 function came from studies by the Altieri's group, which identified TRAP1 as a member of a cytoprotective network selectively active in the mitochondria of tumor tissues. 6 The same group has recently proposed TRAP1 as a novel molecular target in localized and metastatic prostate cancer, 7 and is now involved in a promising preclinical characterization of mitochondria-targeted smallmolecule HSP90 inhibitors. 8,9 Besides some well-characterized TRAP1 functions in mitochondria, during preparation of this manuscript it was reported that interference by HSP90 chaperones triggers an unfolded protein response (UPR) and activates autophagy in the mitochondria of tumor cells.…”
mentioning
confidence: 99%
“…As a member of the Hsp90 family of heat shock proteins known for the familial role played in signal transduction, TRAP1, an intramitochondrial protein, takes a more specialized approach to its molecular chaperone activity by acting as a cytoprotective chaperone (17,19,31,32). Phosphorylation of TRAP1 by PTEN-induced putative kinase 1 protects cancer cells against oxidative stress-induced apoptosis.…”
Section: Trap1-guarding the Furnacementioning
confidence: 99%
“…The Warburg effect, thought to provide the building blocks required by the rapidly proliferating cells and protect the mitochondria from ROS-induced membrane damage and initiation of apoptosis, has been reported in rapidly proliferating cancer, cancer stem cells and normal stem cells (13)(14)(15)(16). Molecular chaperones play a strong role in preventing apoptosis and the mitochondrial molecular chaperone, TRAP1, has been shown to protect cells against ROS-induced damage in cancer cell models (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%